Stereotactic brain injection of human umbilical cord blood mesenchymal stem cells in patients with Alzheimer's disease dementia: A phase 1 clinical trial. Issue 2 (23rd July 2015) - Kim, Hee Jin; Seo, Sang Won; Chang, Jong Wook; Lee, Jung Il; Kim, Chi Hun; Chin, Juhee; Choi, Soo Jin; Kwon, Hunki; Yun, Hyuk Jin; Lee, Jong Min; Kim, Sung Tae; Choe, Yearn Seong; et al.
Abstract: Introduction: We conducted a phase 1 clinical trial in nine patients with mild‐to‐moderate Alzheimer's disease to evaluate the safety and dose‐limiting toxicity of stereotactic brain injection of human umbilical cord blood–derived mesenchymal stem cells (hUCB‐MSCs). Methods: The low‐ (n = 3) and high‐dose (n = 6) groups received a total of 3.0 × 10 6  cells/60 μL and 6.0 × 10 6  cells/60 μL, respectively, into the bilateral hippocampi and right precuneus. Results: No patient showed serious adverse events including fever during the 24‐month follow‐up period. During the 12‐week follow‐up period, the most common acute adverse event was wound pain from the surgical procedure (n = 9), followed by headache (n = 4), dizziness (n = 3), and postoperative delirium (n = 3). There was no dose‐limiting toxicity. Discussion: Administration of hUCB‐MSCs into the hippocampus and precuneus by stereotactic injection was feasible, safe, and well tolerated. Further trials are warranted to test the efficacy. Clinical Trial Registration: ClinicalTrial.gov identifier NCT01297218 and NCT01696591 .